DEVELOPPEMENT URBAIN ET MENACE D’EROSION COTIERE A ABIDJAN - Bouabre Gnoka Modeste (European Scientific Journal, ESJ, 2013)
Urbanization, in fifty years, has resulted in the Ivory Coast, major changes to the plan and organizational physiognomic country, along with the mutation of a real metropolis Abidjan in West Africa and Africa.Yet the bright future of Abidjan is threatened by coastal erosion. There is reason to be concerned about the future of urban development and socio-economic development of the district of Abidjan. Questions about the place of the district of Abidjan in the development of the Ivory Coast are thus put into perspective. In clear, how can we situate the development of the district of Abidjan in relation to that of the Ivory Coast as a whole? How the district of Abidjan has it built in the course of history? How the geographical position of Abidjan, once socio-economic advantage, is transformed today into a real threat destructive?History and geography have contributed significantly erect Abidjan into a true megalopolis Africa. In fact, as true accomplices in a systemic and well-orchestrated collaboration, history and geography have contributed so prodigious, urban development of part of the Ivory Coast that would be called Abidjan.However, this becoming the glorious megalopolis septantenaire, with a strong legacy port, airport, industrial and commercial is now paradoxically threatened by what had formerly done his dual position sea and lagoon. Indeed, the devastating attacks of coastal erosion are now Abidjan in a posture of expectation, to see danger and decline.